The first Tibetan serial: August Hermann Francke's La-dvags-kyi-ag-bâr [La-dwags kyi xag-bvar] (1904 - 1907) ; facsimile of a unique set in the archives of the Evangelische Brüderunität, Herrnhut - Walravens, Hartmut; Engelhardt, Isrun (Neuerwerbungen der Ostasienabteilung / Sonderheft, 2010)
Enth.: La-dwags kyi xag-bvar